The Influence of Ease of Use and Service Quality on Loyalty in Traveloka Platform - Darmadji, Reza; Dewi, Citra Kusuma (PT. EQUATOR SINAR AKADEMIA, 2025)
This study aims to test the quality of service and smoothness of use on loyalty mediated by satisfaction and brand image in the context of Traveloka as one of Indonesia’s leading online travel agent (OTA) platforms. Despite growing attention to digital service experiences, limited research has integrated these four constructs within a comprehensive model. This study uses quantitative techniques by applying a survey to 400 Traveloka users who have made transactions in the past 6 months. Information will be analyzed from Structural Equation Modeling with Partial Least Squares techniques. The study resulted that the perception of smooth use and service quality contributed to satisfaction and brand image. Then satisfaction and brand image contributed to loyalty. This study confirms the partial mediation function of satisfaction and brand image on the relationship between each independent variable and its dependent variable. These findings indicate that digital usability and service performance indirectly shape customer loyalty through perception and emotional responses. Overall, the study contributes to the understanding of loyalty formation on OTA platforms and provides practical implications for improving interface design and service delivery strategies to strengthen consumer retention related to strict digital tourism.